Синтез цифровой системы управления линейным электромеханическим объектом в каноническом фазовом пространстве - Волянский, Роман Сергеевич; Садовой, Александр Валентинович; Шрамко, Юрий Юрьевич; Сохина, Юлия Витальевна; Волянская, Нина Викторовна (Национальный технический университет "Харьковский политехнический институт", 2019)
Разработаны методологические основы синтеза цифровых систем управления линейными электромеханическими объектами. Предлагаемый подход базируется на матричном обобщении модифицированного принципа симметрии в непрерывном времени с последующим преобразованием передаточной функции регулятора в Z-форму и формирования управляющего воздействия при помощи нелинейной активационной функции. Рассмотрен синтез одномерного регулятора для обобщенного динамического объекта и установлены закономерности формирования весовых коэффициентов регулятора. Синтезирован регулятор скорости для двигателя постоянного тока

The paper deals with the development of methodological backgrounds for design of discrete-time control systems for linear electromechanical objects. We suggest designing of such systems by considering modified symmetry principle and generalizing it for multi input multioutput linear dynamical objects. According to this principle, we define matrix transfer function of controller and split it into linear, integral and parallel parts. Matrix transfer function of each part is transformed into Z-formin separate way. We use nonlinear bounded matrix-functions to limit produced control sig-nal. Then, we consider third order generalized dynamical object todefine regularity of controller’s terms. It is shown that ifone use backward difference approximation for derivative operator, he can find controller terms are under distribution, which used binomial factors. W e define controller al -gorithm as function of current and previous values of control variable. At third, we show some drawbacks for controller with deep prehistory and we eliminate these drawbacks by performing several coordinate transformations according to object’s mesh equations. These transformations make it possible to rewrite control algorithm as function of control variable and inner ones. At fourth, we consider synthesis of speed controller for DC electric drive and approve our methods by simulating results. At last, we make the conclusions and the recommendations/
Synthesis of a digital control system for a linear electromechanical object in canonical phase space
Keywords: Линейный цифровой регулятор; z-преобразование; нелинейное управление; Linear discrete-time controller; z-transformation; nonlinear control